2011
DOI: 10.1007/s00018-007-7471-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of cell signaling by glypicans

Abstract: Signaling peptides of the extracellular environment regulate cell biological processes underlying embryonic development, tissue homeostasis, and pathophysiology. The heparan sulphate proteoglycans, glypicans, have evolved as essential modulators of key regulatory proteins such as Wnt, Bmp, Fgf, and Shh. By acting on signal spreading and receptor activation, glypicans can control signal read-out and fate in targeted cells. Genetic and embryological studies have highlighted that glypicans act in a temporal and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 62 publications
2
130
0
Order By: Relevance
“…75 Kny is a member of the glypican family of heparan sulfate proteoglycans that interact with multiple signaling ligands, and therefore, the phenotype might result from pleiotropic effects on signaling pathways activated by other heparan sulfate binding factors. 79 However, in the context of convergent extension, Kny does not appear to regulate Hedgehog, fibroblast growth factor or bone morphogenetic protein signaling. 75,76 Glypican-4, a homolog of Knypek, has also been shown to act in conjunction with Wnt11 and Dishevelled to regulate convergent extension cell movements in Xenopus via non-canonical Wnt signaling.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…75 Kny is a member of the glypican family of heparan sulfate proteoglycans that interact with multiple signaling ligands, and therefore, the phenotype might result from pleiotropic effects on signaling pathways activated by other heparan sulfate binding factors. 79 However, in the context of convergent extension, Kny does not appear to regulate Hedgehog, fibroblast growth factor or bone morphogenetic protein signaling. 75,76 Glypican-4, a homolog of Knypek, has also been shown to act in conjunction with Wnt11 and Dishevelled to regulate convergent extension cell movements in Xenopus via non-canonical Wnt signaling.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Gpcs are evolutionarily conserved proteins found in organisms as distinct as nematodes, fruit flies and mammals (De Cat and David, 2001;Fico et al, 2007;. The human and mouse genome contain six Gpc family members, Gpc-1 to Gpc-6 in humans and gpc-1 to gpc-6 in mice (De Cat and David, 2001;Fico et al, 2007;) whereas five gpc-like genes have been identified in zebrafish Topczewski et al, 2001), two in Drosophila (dally and dally-like; Baeg et al, 2001;Nakato et al, 1995) and two in C. elegans (gpn-1 and lon-2; Gumienny et al, 2007;Hudson et al, 2006).…”
Section: Evolutionary Originsmentioning
confidence: 99%
“…The amino acid sequences of mammalian Gpc vary from being 17% to 63% identical. However, sequence relationships and exon organizations suggest that mammalian gpcs consist of two distinct subfamilies (De Cat and David, 2001;Fico et al, 2007;. The first subfamily includes gpc-1, -2, -4 and -6 genes with amino acid sequence homology ranging from 40-60% and composed of nine exons.…”
Section: Evolutionary Originsmentioning
confidence: 99%
See 2 more Smart Citations